Exploring the interfacial dynamics of unilamellar and multilamellar cationic liposomes on SiO2 and their interactions with membrane-active peptide - Tae, Hyunhyuk (2024)
Understanding the interplay between lipid assemblies and solid supports is crucial for advancing model membrane systems and biomedical applications. This study investigates the interfacial behaviors of unilamellar and multilamellar cationic liposomes on silicon dioxide and their interactions with a membrane-active AH peptide. Using QCM-D monitoring, unilamellar liposomes were found to rapidly form SLBs through one-step adsorption kinetics, whereas multilamellar liposomes exhibited slower adsorption. Further addition of liposomes caused fusogenic interactions with SLBs, where multilamellar liposomes formed more rigid lipid membranes. Upon AH peptide exposure, unilamellar-based lipid membranes showed higher susceptibility to structural transformations, achieving complete SLB formation, while multilamellar-based lipid membranes displayed reduced sensitivity and retained residual viscoelastic components, indicative of incomplete SLB formation. These findings underscore the significant influence of liposome lamellarity on their interfacial dynamics and peptide interactions, crucial for designing effective lipid-based delivery and sensing systems.